Women with breast cancer taking chemotherapy: depression symptoms and treatment adherence (Revista Latino-Americana de Enfermagem, 2014)
Objective to verify depressive symptoms and adherence to chemotherapy among women with breast cancer who are served by the Pharmacy of the Chemotherapy Center of a university hospital. METHOD: cross-sectional study with quantitative approach conducted with 112 women receiving chemotherapy. Structured interviews guided by a script addressing socio-demographic, clinical and therapeutic information, the Morisky Test, and the Beck Depression Inventory were used to collect data. RESULTS: 12.50% and 1.78% of the patients experienced "moderate" and "severe" depression, respectively, while 10.59% did not use antidepressant medication. A statistically significant association was found between levels of depression and the use of antidepressants. Lack of adherence was identified in 46.43% of the participants. CONCLUSION: these findings show the need to regularly screen for depressive symptoms and for adherence to chemotherapy treatment among women with breast cancer, in order to provide early detection and appropriate treatment centered on patients, and to improve their quality of life.